Nosocomial Respiratory Viral Infection in the Neonatal Intensive Care Unit - Vain, Nestor E. (American Journal of Perinatology, 2020)
Infections caused by respiratory viruses in neonates during their stay in the neonatal intensive care unit (NICU) are more frequent than generally suspected. Respiratory syncytial virus (RSV), a highly contagious pathogen, is the most common etiologic agent, and it carries a high risk of nosocomial spread. During the RSV season, overcrowding of the NICU, shortage of staff, and unrestricted visitors are factors predisposing outbreaks. Since signs and symptoms of RSV infections are no specific, a high index of suspicion is essential to prevent or limit epidemics. The etiologic agent should be confirmed and polymerase chain reaction (PCR) is the gold-standard test. Shedding of the virus by infected preterm infants is prolonged and RSV lasts for several hours on countertops and other surfaces. The first case should be isolated and strict cohorting must be instituted. Compliance with hand washing must be warranted. Wearing gowns and gloves may help. The severity of nosocomial RSV infections tends to be higher than that of those community acquired. There is no uniform recommendation to start palivizumab during hospital stay of premature and high-risk infants. The use of this monoclonal antibody to stop or limit the spread of outbreaks is controversial. It is recommended by some professional organizations and not by others but its use during large outbreaks in infants at risk who share the room with infected neonates is not uncommon.Key Points
Keywords: respiratory syncytial virus; NICU outbreak; nosocomial infections; newborn